Peranan Pak Remaja Dalam Perilaku Bersyukur Atas Pemeliharaan Allah Dalam Bentuk Menjaga Dan Melestarikan Alam (Kejadian 1:26 dan Kejadian 2:15)Kelas Vii Semester Genap - Edwin Hendry; Kondrat Boangmanalu; Rasme Sinulaki (Universitas Maritim AMNI Semarang, 2024)
Understanding the human responsibility to preserve and care for nature given by God needs to be instilled from an early age, especially in teenagers. This study examines the role of Christian Religious Education (CRE) for teenagers in fostering a grateful attitude through the preservation of nature based on Genesis 1:26 and 2:15. This research is written using a descriptive qualitative method by exploring various sources such as books, the Bible, and journals related to the role of CRE for teenagers, which are used as references for this journal. The findings indicate that many teenagers today do not want to take care of and preserve their surroundings, such as disposing of waste properly, and many teenagers litter and do not maintain the environment. Therefore, as a research team, we attempt to analyze various problems concerning the environment and the role of CRE for teenagers in protecting and preserving nature.